2001
DOI: 10.1097/00002030-200105250-00005
|View full text |Cite
|
Sign up to set email alerts
|

Increased abdominal visceral fat is associated with reduced bone density in HIV-infected men with lipodystrophy

Abstract: Lumbar spine bone density is reduced in association with increased visceral fat in HIV-infected men with lipodystrophy. Further studies are needed to determine the mechanisms of osteopenia in HIV lipodystrophy and whether increased marrow fat occurs in such patients and affects bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 19 publications
3
69
1
3
Order By: Relevance
“…In addition, antiretroviral treatment and mainly protease inhibitors are associated with reduced BMD, although the results of different studies are controversial [26,30,31]. Recently, the long-term adverse events from highly active antiretroviral therapy administration, especially lipid and glucose metabolism disorders, are studied, but the results are not consistent as well [32][33][34]. In our study, the exact mechanism for the more severe bone loss observed in the HIV-positive patients could not be explained by the measurement of bone markers, as we found no significant differences between HIV-positive and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antiretroviral treatment and mainly protease inhibitors are associated with reduced BMD, although the results of different studies are controversial [26,30,31]. Recently, the long-term adverse events from highly active antiretroviral therapy administration, especially lipid and glucose metabolism disorders, are studied, but the results are not consistent as well [32][33][34]. In our study, the exact mechanism for the more severe bone loss observed in the HIV-positive patients could not be explained by the measurement of bone markers, as we found no significant differences between HIV-positive and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to identify risk factors related to these bone disorders [15]. Hyperlipidaemia, lipodystrophy, diabetes and vasculitis have been described as conditions associated with, or related to, bone disorders [16][17][18] and some risk factors have been suggested, such as alcohol abuse, smoking, hyperlactataemia and corticosteroid use [16,[19][20][21][22][23]. It has also been suggested that bone loss could be the consequence of HIV infection itself [7,11,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…110 Furthermore, a higher degree of visceral obesity was strongly associated with lower trabecular bone density at the lumbar spine, as detected by quantitative computed tomography. 115 This raises the issue of whether a low BMD could result from HIV infection, metabolic complications during antiretroviral therapy, or a combination thereof.…”
Section: Hiv/haart and Cvdmentioning
confidence: 99%